Effect of gender on the utilization of maternal and child health services among pastoralist caregivers in Somali region of Ethiopia (2021)
Ethiopia has made great effort in recent years to improve maternal and child health outcomes, however the uptake of services by women in the pastoralist communities of the country is still very low. This study was a cross-sectional study aimed to identify the effect of gender on the utilization of health services among pastoralists women. The study was conducted in Somali Region of Ethiopia between February and March 2020. A mix of qualitative and quantitative methods was used, and study population were married caregivers aged 15years and above. Bivariate analysis was done using t test and chi-square to test association among variables and p value was set at significant level of 5%. Husbands were reported as the main influence of the respondents’ decision about almost all the key households’ activities including health care seeking and financial decision making. Almost all caregivers (93.6%) who used the health facility took permission from their husbands and the test of association shows significant relationship between level of education and permission from respondents’ husbands which decreases with increasing level of education, p<0.05) but not affected by age. The care givers visited the health facilities because of their children more than themselves (58 per cent compared to 49.5 per cent for themselves) due to fear of being attended to by male health work. The study demonstrated the negative effect of gender inequities on health care seeking behaviours with women having limited control over family resources and decision-making over their health or that of their children.